2012
DOI: 10.1083/jcb.201204098
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-dead ATM protein causes genomic instability and early embryonic lethality in mice

Abstract: Expression of a kinase-deficient ATM protein leads to severe genomic instability and embryonic lethality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 52 publications
8
100
0
Order By: Relevance
“…Previous ATM kinase inhibitor studies described DNA repair defects in cells that are not observed in ATM-null cells, suggesting that even the inactivated protein has roles in DNA repair (56,57). This was supported by two recent publications showing that the presence of full-length, kinase-dead ATM results in early embryonic lethality in mouse models (58,59). The enzymatically inactive ATM lacks dominant-negative interfering activity and yet interferes with homologous recombination to a greater extent than seen in ATM-null cells.…”
Section: Discussionsupporting
confidence: 69%
“…Previous ATM kinase inhibitor studies described DNA repair defects in cells that are not observed in ATM-null cells, suggesting that even the inactivated protein has roles in DNA repair (56,57). This was supported by two recent publications showing that the presence of full-length, kinase-dead ATM results in early embryonic lethality in mouse models (58,59). The enzymatically inactive ATM lacks dominant-negative interfering activity and yet interferes with homologous recombination to a greater extent than seen in ATM-null cells.…”
Section: Discussionsupporting
confidence: 69%
“…1, C and D), indicating that a portion of HR reduction may be specific to ATM kinase inactivation by the inhibitors. It is possible that catalytically inactive ATM may interfere with HR as proposed recently (19,20,37,38) Fig. 2A), suggesting that ATM is dispensable for HR, including that controlled by ␥-H2AX.…”
Section: H2axmentioning
confidence: 99%
“…2) Because poly(ADP-ribose) polymerase (PARP) inhibition selectively kill cells defective for HR (16), synthetic lethality caused by combined deficiency of ATM and PARP1 or PARP2 may be due to synergistic impacts on ATMdependent HR and repair function of PARP1/2 (17,18). In fact, cells carrying homozygous ATM kinase-dead mutations display HR defects and elevated sensitivity to PARP inhibition (19,20).…”
mentioning
confidence: 99%
“…In addition to this rationale, there is precedent for pharmacologic inhibition of such kinases that can be extrapolated from animal studies where a defective kinase is more detrimental to the animal than a nonexpressed kinase. For instance, ATM knockout mice are viable and recapitulate A-T syndrome, whereas mutated "kinase dead" ATM results in embryonic lethality (65). Kinase inhibitors may have effects similar to the kinase-dead mutants; they not only inactivate the kinase target, but also leave the catalytically inactive kinase to block access to site of DNA damage from other proteins that would initiate alternative repair pathways.…”
Section: Therapeutic Opportunities In Atmdeficient Cancers: Inducing mentioning
confidence: 99%